2020
DOI: 10.3390/molecules25051091
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Terpene Profiles of Thymus vulgaris in Water Deficit Stress Response

Abstract: Thyme (Thymus spp.) volatiles predominantly consisting of monoterpenes and sesquiterpenes, serve as antimicrobial, antiseptic and antioxidant in phytomedicine. They also play a key role in plants as secondary metabolites via their potential role against herbivores, attracting pollinators and abiotic stress tolerance. Plant volatiles are affected by different environmental factors including drought. Here, the effect of prolonged water deficit stress on volatile composition was studied on the sensitive and toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 48 publications
1
59
1
1
Order By: Relevance
“…Monoterpene emission has been previously shown to induce heat stress tolerance in several species [ 16 , 23 , 36 ]. For instance, Quercus ilex leaves fumigated with monoterpenes had a lower decline in photosynthesis compared to non-fumigated leaves when exposed to high temperatures [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Monoterpene emission has been previously shown to induce heat stress tolerance in several species [ 16 , 23 , 36 ]. For instance, Quercus ilex leaves fumigated with monoterpenes had a lower decline in photosynthesis compared to non-fumigated leaves when exposed to high temperatures [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some plants accumulate osmolytes such as proline, glycine betaine and soluble sugars to protect themselves and to alleviate the drought stress condition [15][16][17]. Recent studies reported that some secondary metabolites synthesized in plant organs such as volatile compounds terpens [18] and some phytohormones such as brassinolide [19] alleviated the effect of drought stress on plants by improving the plant's defense system. The apple (Malus domestica Borkh.…”
Section: Introductionmentioning
confidence: 99%
“…The high amount of these compounds in belowground organs, which is found in all ontogenetic stages for gentians [ 20 , 37 ], may imply a response to specific biotic pressures. However, more information regarding species autecology (i.e., photosynthesis, morphology, biotic interactions) would provide a better understanding of plant–environment relations among gentians [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%